Utilities Reforms And Corruption In Developing Countries - Estache, Antonio 1957- (The World Bank, 2006)
This paper shows empirically that "privatization" in the energy, telecommunications, and water sectors, and the introduction of independent regulators in those sectors, have not always had the expected effects on access, affordability, or quality of services. It also shows that corruption leads to adjustments in the quantity, quality, and price of services consistent with the profit-maximizing behavior that one would expect from monopolies in the sector. The results suggest that privatization and the introduction of independent regulators have, at best, only partial effects on the consequences of corruption for access, affordability, and quality of utility services